Predicting the return of bladder function following vaginal native tissue repair using data from a suprapubic catheter regimen. Issue 7 (3rd August 2021) - Hines, Katherine N.; McKenzie, Collin; Overholt, Tyler; Mirzazadeh, Majid; Matthews, Catherine A.; Schachar, Jeffrey; Russel, Greg; Lentz, Samuel
Abstract: Aims: To evaluate time to return of normal voiding function following native tissue vaginal reconstruction and evaluate risk factors for postoperative urinary retention (POUR). Methods: A retrospective cohort analysis of women undergoing vaginal reconstruction and suprapubic catheter with standardized regimen for voiding trials. Postvoid residual <150 ml at 4 h post catheter clamping was used as surrogate marker for return of bladder function. Univariate and multivariate regression analyses were used to identify risk factors for return of bladder function >4 days after surgery. Results: Between 2013 and 2018, 148 women underwent surgery, 124 were analyzed. Mean age was 67 years (±11.1), 62.9% ( n  = 78) had greater than or equal to stage 3 prolapse. Mean time to return of bladder function: 4.1 days (±3.1). Significant risk factors for >4 days to return of bladder function on univariate analysis included (mean ± SD): surgery length (150.4 min ±44.6) (odds ratio [OR], 1.24; confidence interval [CI], 1.12, 1.38); anesthesia length (228.1 min ±53.5) (OR, 1.12; CI: 1.04, 1.23); length of stay (2.2 days ±2.7) (OR, 2.43; CI: 1.11, 5.35); hysterectomy (OR, 3.10; CI: 1.39, 6.90); estimated blood loss (124.4 ml ±64.8) (OR, 1.39; CI: 1.04, 1.87). Postmenopausal status was protective (OR, 0.17; CI: 0.03, 0.92.). On multivariate analysis, significant findings were diabetes mellitus (OR, 0.18; CI: 0.04, 0.93) and surgery length (OR, 1.21; CI: 1.06, 1.38). Conclusions: Hysterectomy, surgical length and estimated blood loss were significantly associated with delayed return of bladder function after native tissue vaginal reconstruction. This data can help clinicians tailor postoperative voiding trials after failed initial attempt.